European Consumers' Attitude towards Insects as an Alternative Source of Protein. The Case of Poland - Anna DANKOWSKA; Anna BONA; Patrycja KUJAWA (Communications of International Proceedings, 2020)
Edible insects are generally high in protein and can be considered as meat substitutes. Nevertheless, in European countries edible insects’ consumption is actually very low mainly due to food neophobia. The purpose of this paper was to explore the readiness of people to consume insects as an alternative protein source. An explorative study among 989 consumers was conducted using a questionnaire via the „google forms” and directly as the technique for data collection. Most of respondents do notice the need to search for an alternative source of protein and they are curious about eating a meal containing insects. Main factors that differentiate the opinions regarding eating edible insects as an alternative source of protein were: level of education, gender, age and the product’s degree of processing. People with higher education see a greater need to look for alternative sources of protein than those with basic education. Additionally, men and young people indicate definitely greater desire to consume a meal containing insects than women or older respondents. Most people would be more likely to choose highly processed products. Integration of edible insects as an alternative source of protein into European food culture is possible as people are open and curious. Nevertheless, this process would need an encouragement of consumers using highly processed insects incorporated into ready-to-eat meals, because people seem not to be ready to eat insects in whole form.
Keywords: Insects; Protein; Alternative Source; European Consumers.